KRITIS SOSIAL DALAM KONTEN SASTRA DI TIKTOK @PUJANGGAHALMAHERA00 SEBAGAI MEDIA EKSPRESI GENERASI MUDA TERHADAP FENOMENA SOSIAL DI INDONESIA: PRAGMATIK JACOB L. MEY - Nensilianti Nensilianti; Bungatang Bungatang; Trisnawati Sp (Ma Chung Press, 2026)
This article aims to examine the pragmatic meanings contained in poems that reflect social criticism of natural resource exploitation and power inequality in the Halmahera region. The method used is qualitative with a descriptive approach through pragmatic analysis. The research data consists of poetry excerpts that address environmental issues, legal injustice, and power relations between the state, corporations, and local communities. The analysis is conducted by examining the context of the utterances, implications, metaphors, and rhetorical strategies used to convey social criticism. The results show that these poems employ various pragmatic strategies such as ecological metaphors, rhetorical questioning, repetition, and implications to highlight environmental damage caused by mining and plantation activities, development inequality, and the lack of protection for local communities. Furthermore, these poems demonstrate the irony between the narrative of independence and national development and the social realities faced by local communities.